Keputusan Petani Padi Tentang Penggunaan Pestisida Kimia dan Faktor Penentunya - Pudjiastuti, Agnes Quartina; Sumarno, Sumarno; Ismindarto, Anang (Hasanuddin University, 2024)
Pests and diseases that attack rice plants will cause quality and production to decline. Increasing use of chemical pesticides will result in the risk of crop failure, degrade soil fertility and produce residue. This research aims to analyze rice farmers decisions in Gandong Village and Bulus Village, Bandung District, Tulungagung Regency regarding the use of chemical pesticides and determining factors. This research uses variables age, education, experience, land area, family members, land status, knowledge, skills, attitudes and farmers' decisions to use chemical pesticides. Survey was used to collect data from 40 farmers in Gandong Village and 40 farmers in Bulus Village. Data were analyzed using multiple linear regression tests and independent t tests. The research results show that rice farmers' decisions in using chemical pesticides were determined by experience, knowledge and skills of the farmers. Rice farmers income in the villages didn’t differ significantly. Keywords: chemical pesticides; 6T principles; rice.